ROOT VOLUME AND DRY MATTER OF PEANUT PLANTS AS A FUNCTION OF SOIL BULK DENSITY AND SOIL WATER STRESS. - Duruoha, Charles; Piffer, Cassio Roberto; Silva, Paulo Roberto Arbex (IRRIGA, 2008)
ROOT VOLUME AND DRY MATTER OF PEANUT PLANTS AS A FUNCTION OF SOIL BULK DENSITY AND SOIL WATER STRESS. Charles Duruoha1; Cassio Roberto Piffer2; Paulo Roberto Arbex Silva2 1United States Department of Agriculture (USDA-ARS), National Soil Dynamics Laboratory, Auburn, AL - U.S.A., duruohan@juno.com 2Departamento de Engenharia Rural, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista, Botucatu, São Paulo 1 ABSTRACT Soil compaction may be defined as the pressing of soil to make it denser. Soil compaction makes the soil denser, decreases permeability of gas and water exchange as well as alterations in thermal relations, and increases mechanical strength of the soil. Compacted soil can restrict normal root development. Simulations of the root restricting layers in a greenhouse are necessary to develop a mechanism to alleviate soil compaction problems in these soils. The selection of three distinct bulk densities based on the standard proctor test is also an important factor to determine which bulk density restricts the root layer. This experiment aimed to assess peanut (Arachis hypogea) root volume and root dry matter as a function of bulk density and water stress. Three levels of soil density (1.2, 1.4, and 1.6g cm-3), and two levels of the soil water content (70 and 90% of field capacity) were used. Treatments were arranged as completely randomized design, with four replications in a 3x2 factorial scheme. The result showed that peanut yield generally responded favorably to subsurface compaction in the presence of high mechanical impedance. This clearly indicates the ability of this root to penetrate the hardpan with less stress. Root volume was not affected by increase in soil bulk density and this mechanical impedance increased root volume when roots penetrated the barrier with less energy. Root growth below the compacted layer (hardpan), was impaired by the imposed barrier. This stress made it impossible for roots to grow well even in the presence of optimum soil water content. Generally soil water content of 70% field capacity (P<0.0001) enhanced greater root proliferation. Nonetheless, soil water content of 90% field capacity in some occasions proved better for root growth. Some of the discrepancies observed were that mechanical impedance is not a good indicator for measuring root growth restriction in greenhouse. Future research can be done using more levels of water to determine the lowest soil water level, which can inhibit plant growth. KEY WORDS: Soil compaction; water stress; soil bunk; root volume; root growth DURUOHA, C.; PIFFER, C. R.; SILVA, P. R. A. MATÉRIA SECA E VOLUME DE RAÍZES DE PLANTAS DE AMENDOIMEM FUNÇÃO DADENSIDADEE DO DÉFICIT DE ÁGUA DO SOLO. 2 RESUMO O conceito de compactação do solo não inclui apenas a redução do solo, mas também no resultante decréscimo em permeabilidade para trocas gasosas e água, assim como alterações em relação térmica e aumento na resistência mecânica do solo. Um solo compactado pode restringir o desenvolvimento radicular normal da planta. Simulações de camadas de restrição de raízes em casa de vegetação são necessárias para desenvolver mecanismos que reduzam problemas de compactação dos solos. A seleção de três diferentes densidades de solo, baseadas no ensaio de Proctor, é também um fator importante para determinar qual densidade restringe a penetração da raiz. O presente trabalho foi realizado para avaliar o volume e matéria seca radicular em função da densidade do solo e da disponibilidade hídrica em amendoim (Arachis hypogea). Foram utilizados três níveis de densidade do solo (1,2; 1,4 e1,6 gcm-3) e dois níveis de teor de água no solo (70 e 90% da capacidade de campo). Os tratamentos foram inteiramente casualizados com quatro repetições em arranjo fatorial (3 x 2). Os resultados sugerem que a produção de amendoim geralmente responde favoravelmente à compactação subsuperficial, na presença de impedância mecânica elevada. Este resultado claramente indica a habilidade da raiz em penetrar na camada de impedimento com menor densidade. O volume radicular não foi afetado pelo aumento da densidade do solo e esta impedância mecânica aumentou o volume radicular quando as raízes penetraram em barreiras com menor compactação. O crescimento radicular abaixo da camada compactada foi afetado pela barreira imposta. Esta compactação impossibilitou que as raízes crescessem mesmo na presença de teor de água ótimo. O teor de água de 70 % da capacidade de campo (P<0,0001) proporcionou maior proliferação radicular. Foi observado que a impedância mecânica não é um bom indicador para a avaliação da restrição de crescimento radicular no trabalho em casa de vegetação. UNITERMOS: compactação do solo, capacidade de campo e crescimento radicular.